Molluscicidal activity of entomopathogenic fungus, metarhizium anisopliae (Hypocreales: Clavicipitaceae) against golden apple snails, pomacea canaliculata (Architaeniglossa: Ampullariidae) - Mohamad Ikmal Hakim Allahudin; Anis Jazleena Syafiqah Ann Jaisofi; Ma, Nyuk Ling; Thilahgavani Nagappan; Aziz Ahmad; Ng, Lee Chuen; Wahizatul Afzan Azmi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Golden Apple Snails (GAS, Pomacea canaliculata) is known in Malaysia as one of the world’s worst invasive pest species, wreaking havoc on paddy fields by lowering rice yield dramatically. Farmers now employ chemical molluscicides to eliminate GAS, but these are expensive and have serious health and environmental consequences. Biological control agent using entomopathogenic fungus is preferred over chemical molluscicides to control GAS because it is non-toxic, environmentally friendly and cost-effective. This study is aimed to investigate the molluscicidal activity of an entomopathogenic fungus, Metarhizium anisopliae towards GAS adults and eggs. M. anisopliae conidia were subsequently produced into four concentrations (3×104 , 3×105 , 3×106 , and 3×107 conidia/mL) and tested against adults and eggs GAS. The median lethal time (LT50) for the concentration of 3×107 took 5 and 3 days to kill 50% of GAS adults and inhibited 50% of eggs from hatching, respectively. Physiological analysis was also conducted on both GAS adults and eggs. The skin of infected individuals became white and opaque, while internal organs such as the pulmonary sac, digestive tract, and hepatopancreas were visibly destroyed. The colour of GAS eggs turned pale after M. anisopliae infestation and resulted in non-viable eggs. This research shows that M. anisopliae is an effective biological control agent for GAS and has the potential to be used as a targeted bio-molluscicide for GAS management.